Aggregation induced red shift emission of phosphorus doped carbon dots. Issue 51 (23rd June 2017) - Li, Ying; Lin, Hechun; Luo, Chunhua; Wang, Yunqiu; Jiang, Chunli; Qi, Ruijuan; Huang, Rong; Travas-sejdic, Jadranka; Peng, Hui
Abstract : Phosphorous doped carbon dots (P-CDs), prepared by a one-step hydrothermal method, show the phenomenon of aggregation induced red shift emission (AIRSE). Abstract : Phosphorous doped carbon dots (P-CDs) are prepared by a one-step hydrothermal method. The phenomenon of aggregation induced red shift emission (AIRSE) is observed in the obtained P-CDs. The emission wavelength of a P-CD solution can be tuned in the range from 455 nm to 595 nm by changing the solution concentration.